Overexpression of maize transcription factor mEmBP-1 increases photosynthesis, biomass, and yield in rice. (22nd May 2020) - Perveen, Shahnaz; Qu, Mingnan; Chen, Faming; Essemine, Jemaa; Khan, Naveed; Lyu, Ming-Ju Amy; Chang, Tiangen; Song, Qingfeng; Chen, Gen-Yun; Zhu, Xin-Guang
Abstract : Overexpression of the maize transcription factor mEmBP-1 increases photosynthesis, biomass, and yield in rice by up-regulation of genes encoding proteins involved in photosynthetic light reactions and carbon metabolism. Abstract: Identifying new options to improve photosynthetic capacity is a major approach to improve crop yield potential. Here we report that overexpression of the gene encoding the transcription factor mEmBP-1 led to simultaneously increased expression of many genes in photosynthesis, including genes encoding Chl a, b -binding proteins (Lhca and Lhcb), PSII (PsbR3 and PsbW) and PSI reaction center subunits (PsaK and PsaN), chloroplast ATP synthase subunit, electron transport reaction components (Fd1 and PC), and also major genes in the Calvin–Benson–Bassham cycle, including those encoding Rubisco, glyceraldehyde phosphate dehydrogenase, fructose bisphosphate aldolase, transketolase, and phosphoribulokinase. These increased expression of photosynthesis genes resulted in increased leaf chlorophyll pigment, photosynthetic rate, biomass growth, and grain yield both in the greenhouse and in the field. Using EMSA experiments, we showed that mEmBP-1a protein can directly bind to the promoter region of photosynthesis genes, suggesting that the direct binding of mEmBP-1a to the G-box domain of photosynthetic genes up-regulates expression of these genes. Altogether, our results show that mEmBP-1a is a major regulator of photosynthesis, which can be used to increase rice photosynthesis and yield in the field.